Making addictions in standardised screening and diagnostic tools. Issue 3 (1st September 2016) - Dwyer, Robyn; Fraser, Suzanne
ABSTRACT: What counts as a drug problem? What exactly is addiction? What can be done to address it? Researchers work in a wide range of disciplines to answer these questions, often relying upon information collected via screening and diagnostic tools. Typically developed within epidemiological research, these tools establish and stabilise key criteria for identifying problematic substance use and addiction, and these criteria are then deployed to measure the extent and scale of the problems within populations. In this article, we analyse these tools to identify the logics and assumptions at work within them. Recognising that epidemiology constitutes, as much as it measures, the diseases it tracks, this article examines how addiction screening and diagnostic tools go about making the phenomena they purport to track. Our analysis suggests that through processes of reduction, expression, quantification, normalisation and populationisation, addiction screening and diagnostic tools work to establish, standardise and reify addiction as an independent, pre-existing affliction located in individuals. In so doing, they erase the complexities and subjective interpretations of individual experiences. In conclusion, we consider the material effects of defining addiction in certain ways, measuring it in certain communities and contexts, and through certain methods, and designing responses based on these strategies.